2016
DOI: 10.4172/2161-038x.1000182
|View full text |Cite
|
Sign up to set email alerts
|

Role of MR Spectroscopy (H1-MRS) of the Testis in Men with Semen Analysis Altered

Abstract: Purpose: Proton magnetic resonance spectroscopy (1 H-MRS) has been proposed as a tool to assess male infertility providing metabolic signatures related to the spermatogenesis in the testis. This study sought to identify the role of 1 H-MRS in the diagnosis of infertility in patients with semen analysis altered. Materials and Methods:14 patients (27 testicles) with fertility problems and with an altered semen analysis (5 oligospermia, 3 asthenospermia, 6 oligoasthenospermia) and 9 controls (18 testicles) with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 28 publications
6
22
0
1
Order By: Relevance
“…The aim of the present study is to assess normal paired testes asymmetry by investigating differences in the biochemical testicular milieu on a 3.0 T system. The main findings are the following: (a) the major metabolic peaks of 1H‐MR spectra in normal adult testes are those of choline, myo‐inositol and lipids, similarly to previous reports (Aaronson et al, 2010; Baleato‐Gonzalez et al, 2015; Firat et al, 2008; Parenti et al, 2016; Storey et al, 2018; Tsili et al, 2016) and (b) although normal paired size testes asymmetry is not confirmed, differences in the biochemical environment of bilateral testes are found; specifically, increase in levels of glutamate and lactate is observed in left normal testis, compared with the right side.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The aim of the present study is to assess normal paired testes asymmetry by investigating differences in the biochemical testicular milieu on a 3.0 T system. The main findings are the following: (a) the major metabolic peaks of 1H‐MR spectra in normal adult testes are those of choline, myo‐inositol and lipids, similarly to previous reports (Aaronson et al, 2010; Baleato‐Gonzalez et al, 2015; Firat et al, 2008; Parenti et al, 2016; Storey et al, 2018; Tsili et al, 2016) and (b) although normal paired size testes asymmetry is not confirmed, differences in the biochemical environment of bilateral testes are found; specifically, increase in levels of glutamate and lactate is observed in left normal testis, compared with the right side.…”
Section: Discussionsupporting
confidence: 88%
“…Currently, scrotal MRI is considered an effective, complementary diagnostic tool for the investigation of abnormal testis (Aganovic & Cassidy, 2012; Mathur, Mills, & Spektor, 2017; Tsili et al, 2014, 2018). 1H‐MRS has recently been added as an adjunct tool to conventional MRI that might serve as a bridge between metabolism and anatomical and physiological changes taking place within previously determined VOIs in normal and pathologic testis (Aaronson et al, 2010; Baleato‐Gonzalez et al, 2015; Firat et al, 2008; Parenti et al, 2016; Storey et al, 2018; Tsili et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parenti et al . found that the height of the choline peak was significantly lower in a group of patients with altered semen parameters compared to a control group with normal spermatogenesis 11 .…”
Section: Introductionmentioning
confidence: 85%
“…Az eddig megjelent cikkek leginkább az alap-MR-szekvenciákat tanulmányozták TART esetében. Az MR-spektroszkópia hasznos lehet a hereállomány funkciójának megítélésében, mivel károsodott here esetében a colin csúcs csökkenést mutat, már a morfológiai elváltozások megjelenése előtt [22,23].…”
Section: Képalkotás -Differenciáldiagnosztikaunclassified